Pneumonia in palliative care patients, part 1 – principles of diagnosis and treatment, hospital-acquired pneumonia, and community-acquired pneumonia - Nowak, Piotr J.; Zasowska-Nowak, Anna (Medycyna Paliatywna/Palliative Medicine, 2018)
Pneumonia is an important problem in patients under palliative care. Its occurrence is associated with increased risk of death and deterioration of quality of life. Establishing a diagnosis and making a decision to introduce or to withhold an antibiotic therapy can be challenging for a physician who takes care of a patient who is often in poor general condition resulting from the advanced main disease. Treatment aimed at alleviating symptoms should be introduced in every case. Causative treatment (antibiotic therapy) regarding its duration, type of applied medications, their doses, and means of administration depends on the etiology and severity of pneumonia. Although the majority of patients under palliative care require antibiotic therapy in certain cases, especially in patients in advanced terminal or agonal states, it can be futile. Diagnostic and therapeutic decisions should be made individually after consideration of the patient’s state, prognosis, and preferences.